Lower Bounds of the Resolvent Estrada Indices for Line Graphs and Complementary Graphs - Jia, Shuxiang; Deng, Bo; Ye, Chengfu; Liang, Weilin (Discontinuity, Nonlinearity, and Complexity, 2026)
Let $G$ be a simple graph of order $n$. The resolvent Estrada index of $G$ is defined as $REE(G)=\sum_{i=1}^n {\frac{n-1}{n-1-λ _i }} $, where $λ _1 , λ _2 , … , λ _n $ are the eigenvalues of the adjacency matrix $A(G)$. In this paper, we present several lower bounds of the resolvent Estrada indices for line graphs of any regular graphs and their complementary graphs.